BürgerBusse in Fahrt bringen. Stationen auf dem Weg zum BürgerBus. - Schiefelbusch, Martin (My University, 2015)
Ein Leitfaden zur Einrichtung eines Bürgerbusses mit Beispielen und praktischen Hinweisen für die Umsetzung.

Honorary posts become more and more important in the public passenger transport, especially in rural areas. Due to the problems which have been developed in accordance with the so-called demographic change in rural areas, an economic solution is to be worked out to further provide mobility even in times and areas with a low demand. Flexible service systems by taxi and rental cars resign everywhere where the business is no longer available. Due to this, citizen buses as a new type of offer become more and more important for authorities and transport companies in rural areas. This will also be examined within a federal research project in order to develop a guideline for potential applicants.
Citizen buses: on the growing importance of honorary posts in the public passenger transport.
Keywords: Verkehr; Verkehrsplanung; ÖPNV; Ländlicher Raum; Mobilität; Busverkehr; Bürgerengagement; Bürgerbus